1982
DOI: 10.1515/cclm.1982.20.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transient Hypoxia in Skeletal Muscle on Enzyme Activities in Lymph and Plasma

Abstract: Lindena, Küpper and Träutschold: Skeletal muscle hypoxia and enzyme activities in lymph and plasma 95 J. Gin. Chem. Clin. Biochem. Vol. 20,1982, pp. 95-102 (Received July 7/October 21,1981) Summary: The effect of hypoxia lasting one hour on the hind leg muscle of anaesthetised dogs was investigated. Ten enzyme activities in plasma and leg lymph, and the lymphatic transport of these enzymes were investigated. Enzymes with high activity in muscle, like creatme kinase, lactate dehydrogenase, malate dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Blood CK activity does not depend on the site of sampling (Henry et al, 1970;Lindena et al, 1982a), but an incorrect venepuncture can result in higher activities through puncture of underlying muscles (Fayolle et al, 1992). Identical CK activity was reported in serum and heparinized plasma (Cairns et al, 1978), but we found higher activities in serum, probably owing to leakage of CK from platelets (Auguste, 1992).…”
Section: Reference Values and Physiological Factors Of Variationsupporting
confidence: 54%
See 3 more Smart Citations
“…Blood CK activity does not depend on the site of sampling (Henry et al, 1970;Lindena et al, 1982a), but an incorrect venepuncture can result in higher activities through puncture of underlying muscles (Fayolle et al, 1992). Identical CK activity was reported in serum and heparinized plasma (Cairns et al, 1978), but we found higher activities in serum, probably owing to leakage of CK from platelets (Auguste, 1992).…”
Section: Reference Values and Physiological Factors Of Variationsupporting
confidence: 54%
“…It also depends on the type of muscle: CK activity is more elevated in fast-contracting (e.g.m. sartorius) than in slow-contracting (m. gastrocnernius) muscles (Lindena et al, 1982a). There are no sex-related differences (Clampitt and Hart, 1978).…”
Section: Distribution In the Organs Of The Dogmentioning
confidence: 97%
See 2 more Smart Citations
“…The second hypothesis is compatible with metabolic impairment of skeletal muscles during fetal hypoxia resulting in CK release to lymphatic space. LINDENA et al [14] demonstrated six times higher CK activity in lymph as compared to serum. Lymph flow is related to muscle activity.…”
Section: Discussionmentioning
confidence: 95%